OPTIMALISASI LAHAN SAWAH TADAH HUJAN MELALUI DIVERSIFIKASI DENGAN TANAMAN HORTIKULTURA SEBAGAI UPAYA PENINGKATAN PENDAPATAN PETANI DI INDONESIA: LITERATUR RIVIEW - kahilda Inshani Noe jehamur; Yohanes Freadyanus Kasi; Karolus Tuke Pasa; maria elisabet Ga'a (Fakultas Pertanian dan Peternakan Universitas Muhammadiyah Bengkulu, 2026)
Rainfed rice fields have extensive potential in Indonesia, but their utilization is not optimal. Dependence on rainfall and the lack of permanent irrigation results in a cropping pattern of only once a year, with rice as the commodity. This condition results in idle land during the dry season and impacts low farmer income. This study aims to examine the optimization of rainfed rice fields through diversification with horticultural crops as an effort to increase farmer income in Indonesia. The method used is a literature review by analyzing 10 scientific journals obtained through Google Scholar published by reviewing various research results related to rainfed land centers. The results show that optimization through diversification into horticultural crops such as chilies, tomatoes, mustard greens, and spices can increase farmer income. Horticultural crops have high economic value, a fast harvest cycle of 2-3 months, and stable market demand. The success of optimization is largely determined by the efficient use of farm inputs and the role of agricultural extension workers as facilitators. In conclusion, optimizing rain-fed rice fields with horticultural crops is an effective strategy for increasing farmer income in Indonesia if supported by efficient farming practices, strengthening farmer groups, and improving market access.